Feeding Habits of Amazonian Freshwater Turtles (Podocnemididae and Chelidae) from Peru - de Oliveira Ferronato, Bruno; Piña, Carlos Ignacio; Molina, Freddy Cochachez; Espinosa, Renato A; Morales, Víctor R (Chelonian conservation and biology, 2013)
We describe here the feeding habits of the Yellow-spotted River turtle (Podocnemis unifilis) (n  =  20), Geoffroy's side-necked turtle (Phrynops geoffroanus) (n  =  10), and Gibba turtle (Mesoclemmys gibba) (n  =  4) from central Peru, Pasco Department, and evaluate food overlaps among them. Podocnemis unifilis showed a generalist feeding habit, ingesting animal and plant matter, but tending to be herbivorous, because plant matter made up 62.9% of the volume vs. 3.9% for animal material. The most important items in P. unifilis diet were seeds from the Fabaceae (Leguminosae) family and bark. Podocnemis geoffroanus and M. gibba also had generalist feeding habits. The most important items for P. geoffroanus were insects, especially Libellulidae larvae, and plant material. Mesoclemmys gibba ingested insects, fish, crustaceans, unidentified plant matter, bark, leaves, stem, and algae, with plant matter being more representative by frequency and volume. Low dietary overlap was observed between P. unifilis and P. geoffroanus, and both species appeared to overlap with M. gibba. To our knowledge, this is the first quantitative dietary study of Peruvian freshwater turtles, and the first diet analysis of wild M. gibba in the Amazon basin.